Kajian Organologi Pembuatan Alat Musik Tradisi Saluang Darek Berbasis Teknologi Tradisional - Ediwar Ediwar; Rosta Minawati; Febri Yulika; Hanefi Hanefi (LP2M ISBI Bandung, 2019)
ABSTRACTThe music of Saluang Darek wind instrument is Minangkabau traditional music that uses the musical instrument of aerophone classification (air as the main source of vibration) and the kind of end-blown without-block flutes musical instrument, and this musical instrument is used to accompany Minangkabau songs or dendangs. Saluang Darek is made of bamboo. The best bamboos for making Saluang Darek are (1) Talang bamboo (Schizostachyum brachycladum kurz), (2) Buluah Kasok bamboo (Gingantocholoa apus), (3) Tamiang bamboo (Schizostachyum zollingeri steud), and (4) Cimanak bamboo (Schizostachyum longispiculatum). The production of Saluang Darek musical instrument uses the traditional technology by still maintaining the quality of instrument that's ready to be used for the performing arts particularly in accompanying dendang. The method used in this research was the qualitative method by using the approach of organology study. Data were collected through the library research, observation, interview, and documentation. This study found the importance of the musical instrument study in order to give information for the musicologists' and ethnomusicologists' works, at once conserve the musical culture in West Sumatera.Keywords: Saluang Darek, Organology, Aerophone, Traditional technology ABSTRAKMusik tiup Saluang Darek adalah musik tradisional Minangkabau yang menggunakan alat musik klasifikasi Aerophone (udara sebagai sumber getaran utama) dan alat tiup jenis end-blown without-block flutes digunakan untuk mengiringi nyanyian atau dendang Minangkabau. Alat musik Saluang darek terbuat dari bambu, yang paling baik untuk alat musik Saluang adalah (1) bambu talang ( Schizostachyum brachycladum kurz), (2) bambu buluah kasok (Gingantocholoa apus), (3) bambu tamiang (scizostachyum zollingeri steud), (4) bambu cimanak (Schizotachyum longispiculatum). Pembuatan alat musik Saluang darek menggunakan teknologi tradisional dengan tetap menjaga kualitas alat yang siap dipakai untuk seni pertunjukan dalam mengiringi dendang. Metode yang dipakai dalam penelitian ini adalah metode kualitatif dengan pendekatan kajian organologi. Data dikumpulkan melalui studi pustaka, observasi, wawancara dan dokumentasi. Kajian ini mendapati pentingnya kajian instrumen musik untuk memberikan infomasi dalam pekerjaan musikolog dan etnomusikolog, sekaligus pelestarian budaya musikal di Sumatera Barat. Kata kunci: Saluang darek, Organology, Aerophone, Teknologi tradisional ABSTRACTThe music of Saluang Darek wind instrument is Minangkabau traditional music that uses the musical instrument of aerophone classification (air as the main source of vibration) and the kind of end-blown without-block flutes musical instrument, and this musical instrument is used to accompany Minangkabau songs or dendangs. Saluang Darek is made of bamboo. The best bamboos for making Saluang Darek are (1) Talang bamboo (Schizostachyum brachycladum kurz), (2) Buluah Kasok bamboo (Gingantocholoa apus), (3) Tamiang bamboo (Schizostachyum zollingeri steud), and (4) Cimanak bamboo (Schizostachyum longispiculatum). The production of Saluang Darek musical instrument uses the traditional technology by still maintaining the quality of instrument that's ready to be used for the performing arts particularly in accompanying dendang. The method used in this research was the qualitative method by using the approach of organology study. Data were collected through the library research, observation, interview, and documentation. This study found the importance of the musical instrument study in order to give information for the musicologists' and ethnomusicologists' works, at once conserve the musical culture in West Sumatera.Keywords: Saluang Darek, Organology, Aerophone, Traditional technology ABSTRAKMusik tiup Saluang Darek adalah musik tradisional Minangkabau yang menggunakan alat musik klasifikasi Aerophone (udara sebagai sumber getaran utama) dan alat tiup jenis end-blown without-block flutes digunakan untuk mengiringi nyanyian atau dendang Minangkabau. Alat musik Saluang darek terbuat dari bambu, yang paling baik untuk alat musik Saluang adalah (1) bambu talang ( Schizostachyum brachycladum kurz), (2) bambu buluah kasok (Gingantocholoa apus), (3) bambu tamiang (scizostachyum zollingeri steud), (4) bambu cimanak (Schizotachyum longispiculatum). Pembuatan alat musik Saluang darek menggunakan teknologi tradisional dengan tetap menjaga kualitas alat yang siap dipakai untuk seni pertunjukan dalam mengiringi dendang. Metode yang dipakai dalam penelitian ini adalah metode kualitatif dengan pendekatan kajian organologi. Data dikumpulkan melalui studi pustaka, observasi, wawancara dan dokumentasi. Kajian ini mendapati pentingnya kajian instrumen musik untuk memberikan infomasi dalam pekerjaan musikolog dan etnomusikolog, sekaligus pelestarian budaya musikal di Sumatera Barat. Kata kunci: Saluang darek, Organology, Aerophone, Teknologi tradisional